2019
DOI: 10.1016/j.ijpam.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Universal screening program for lipid disorders in 2-10 years old Lebanese children

Abstract: IntroductionDyslipidemia has been recognized as a risk factor for cardiovascular diseases. Studies have showed that the development of atherosclerotic lesions begins in childhood and progresses throughout life. While the prevalence of dyslipidemia in adults has been reported to be 10 times higher in Lebanon compared to Western countries, data on the prevalence of dyslipidemic children in Lebanon is lacking.ObjectivesThis study was conducted to assess the benefit of a protocol for universal screening for lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Dyslipidemia is a serious metabolic disorder accompanied by lipid abnormalities such as elevated TAG, VLDL-C, TC, LDL-C and decreased HDL-C (Sun et al, 2018). Management of dyslipidemia is important since it is a risk factor for cardiovascular diseases (Buşilȃ et al, 2017). One possible mechanism by which dyslipidemia leads to cardiovascular disorders is the generation of free radicals and oxidative stress (Singh et al, 2016).…”
Section: Dyslipidemiamentioning
confidence: 99%
“…Dyslipidemia is a serious metabolic disorder accompanied by lipid abnormalities such as elevated TAG, VLDL-C, TC, LDL-C and decreased HDL-C (Sun et al, 2018). Management of dyslipidemia is important since it is a risk factor for cardiovascular diseases (Buşilȃ et al, 2017). One possible mechanism by which dyslipidemia leads to cardiovascular disorders is the generation of free radicals and oxidative stress (Singh et al, 2016).…”
Section: Dyslipidemiamentioning
confidence: 99%
“…This is consistent with other studies such as the CARDIAC Project where 28.6% of 20 266 fifth-grade children in West Virginia found to have dyslipidemia did not have a positive family history, 24 and a study in Lebanon where 37.7% of children aged 2 to 10 years with dyslipidemia did not possess any risk factor. 25 The evidence review of the 2011 NHLBI/AAP guidelines concluded that 30% to 60% of children with dyslipidemia would be missed if lipid screening were not universal. 3 Thus, our results lend further support for the importance of universal rather than targeted lipid screening for the identification of children with dyslipidemia who may not otherwise be recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is one of the risks for the progression of cardiovascular diseases such as atherosclerosis, ischemic heart disease, stroke, and coronary heart disease because it leads to the synthesis of free radicals and oxidative stress (Georges et al, 2019;Singh et al, 2016). Conventional medications for dyslipidemia include lovastatin, atorvastatin, simvastatin, and pravastatin which have adverse effects, i.e., myopathy, rhabdomyolysis, and myalgia (Shin et al, 2014;Chu et al, 2015;Wat et al, 2016).…”
Section: Dyslipidemiamentioning
confidence: 99%